Considerations and Determinants of the Rehabilitation and Reuse of Historic Buildings - نانو نغم (Latakia University Journal -Engineering Sciences Series, 2021)
The urban and architectural heritage is an important part of the national and international cultural heritage. Being an important link of development for all humanity. An important factor of cultural, social and economic development if we know how to employ it in a way that is compatible with the data of the times and its needs, it is an inspiring source of creativity in rooting civilized values, up to original and contemporary architecture that expresses the identity of the nation and the depth of its cultural affiliation. And the continuity of preserving the architectural heritage can only be achieved and sustained With all the components of the environment it embraces, and improving the conditions of the population, especially those surrounding it culturally, socially and economically. It includes the theoretical framework for the research, the general concept of historic buildings and the dangers threatening them, whether they are the result of natural factors or the result of human action, the importance of architectural and urban heritage, how to preserve it, levels of intervention in the processes of preserving heritage buildings, determinants and considerations to be taken into account when reuse antique buildings and how to ensure continuity Preserving archaeological buildings when rehabilitating. The research also includes the various directions for the reconstruction of archaeological buildings destroyed by disasters and armed conflicts in light of global experiences. At the end of the research, a methodological plan was reached. It includes a set of work steps for the rehabilitation and employment of destroyed monuments during the war as a proposal that incl udes the determinants of works in the study of their application in the processes of rehabilitation and reuse of damaged archaeological buildings.